Anticariogenic potential of Lactiplantibacillus plantarum-isolated kimchi in suppression of Streptococcus mutans’ growth - Malathi Ganeson,; Zaleha Shafiei,; Noraziah Mohamad Zin,; Mohd Nizam Lani,; Zamirah Zainal Abidin,; Mazlina Mohd Said, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Kimchi, a lactic acid-fermented vegetable product, is widely recognised for its popularity and health benefits. It contains antimicrobial microorganisms. This study aimed to isolate, characterise, and test antimicrobial activity of kimchi isolates against Streptococcus mutans. Kimchi samples were mixed in MRS broth (1:10 w/v) and incubated overnight at 37 °C. Then, serially diluted 10-folds and spread onto MRS agar to isolate lactic acid bacteria (LAB). Gram staining, catalase, and oxidase tests were performed, followed by API 50 CHL and 16S rRNA sequencing analysis to identify the most potent strain. Four selected strains, K1, K2, K3, and K4 were identified and determined for their antibacterial activity against S. mutans using agar spot and agar well diffusion methods. Strain K2 with the diameter of the inhibition zone (33.50 ± 5.47 mm), and strain K3 (33.50 ± 3.62 mm) are the strains with the most potential to inhibit S. mutans. However, the cell-free supernatant of strain K2 (9.92 ± 0.58 mm) exhibited higher inhibitory activity than strain K3. Therefore, strain K2 was selected as the most potential strain, identified as Lactobacillus (currently known as Lactiplantibacillus) plantarum 1 in the API web database and confirmed by 16S rDNA gene sequencing as Lactiplantibacillus plantarum strain AMT744129 with 99.3% similarity. Thus, Lactiplantibacillus plantarum strain K2-isolated kimchi has a cariogenic effect and could be potential as an alternative agent in treating dental caries.